2016
DOI: 10.1016/j.ergon.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

UK rail workers' perceptions of accident risk factors: An exploratory study

Abstract: Although non-fatal injuries remain a frequent occurrence in Rail work, very few studies have attempted to identify the perceived factors contributing to accident risk using qualitative research methods. This paper presents the results from a thematic analysis of ten interviews with On Track Machine (OTM) operatives. The inductive methodological approach generated five themes, of which two are discussed here in detail, 'Pressure and fatigue', and 'Decision making and errors'. It is concluded that for companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…These views were supported by an exploratory study of UK rail workers' perceptions of accident risk factors (Morgan et al, 2016 ). This study demonstrated the impact of shift-work, commuting time, work-life balance, and time pressure on perceived stress and fatigue at work.…”
Section: Resultsmentioning
confidence: 92%
“…These views were supported by an exploratory study of UK rail workers' perceptions of accident risk factors (Morgan et al, 2016 ). This study demonstrated the impact of shift-work, commuting time, work-life balance, and time pressure on perceived stress and fatigue at work.…”
Section: Resultsmentioning
confidence: 92%
“…In the railway industry, the interaction between human and organizational factors plays a crucial role in maintaining safe work operations (Morgan et al, 2016). Although major accidents are often attributed to human error alone, it has been argued that organisations are ultimately responsible because they shape the safety climate within which railway workers operate (Itoh, Andersen, & Seki, 2004;Reason, 1997).…”
mentioning
confidence: 99%
“…For the most part, accident investigations across a range of industries already use human factors to explain sociocultural/technical influences on error. The rail industry is no exception and contributory human factors are viewed through the lens of various frameworks, tools and approaches, with many originally developed in other industries and adapted for the rail environment (Morgan et al 2016). Thus, in conjunction with determining the extent to which authority gradients in rail have been investigated, it is important to examine how various techniques seek to understand how communication errors transpire, whether these methods are effective for identifying power distribution in teams, and the impact this may have.…”
Section: Understanding Communication Error In the Rail Environment Bementioning
confidence: 99%
“…Communication error is a human factor in similar, high-risk domains like healthcare and aviation, where frameworks have also been developed to identify contributing factors and develop methods for accident prevention (Morgan et al 2016). On determination of a paucity of literature relating to the influence of authority gradients or power distance and/ or power imbalances within teams in rail, substantive literature from analogous systems mentioned earlier in the paper (e.g., aviation, healthcare) were explored using the same search terms (excluding the term "rail").…”
Section: Review Approachmentioning
confidence: 99%